Dominant Physical Condition Components of Wrestling Athletes in Indramayu Regency - Fajar Itani; Andy Supriady; Nancy Trisari Schiff (STKIP Pasundan Press, 2026)
The purpose of this study was to determine the dominant physical condition components of Indramayu Regency Wrestling Athletes. The method in this study was pre-experimental design with a one-shoot case study design. The population in this study were all 8 Indramayu Regency wrestling athletes. The research sampling technique used Total sampling, so the research sample consisted of 8 athletes. The results of the study showed that the dominant physical condition of Indramayu Regency wrestling athletes showed that the flexibility component was in the good category with a percentage of (39%), while strength was in the sufficient category with a percentage of (23%). Meanwhile, speed was in the sufficient category with a percentage of (12%), and endurance was in the very poor category with a percentage of (50%). These findings indicate that flexibility is the dominant component, while abdominal muscle strength, leg muscle strength, speed, and endurance need to be improved. The conclusion of this study is that the Dominant Physical Condition component of Indramayu Regency Wrestling is flexibility.